Graphene and Beyond: Recent Advances in Two-Dimensional Materials Synthesis, Properties, and Devices - Lei, Yu; Zhang, Tianyi; Lin, Yu-Chuan; Granzier-Nakajima, Tomotaroh; Bepete, George; Kowalczyk, Dorota A.; Lin, Zhong; Zhou, Da; Schranghamer, Thomas F.; Dodda, Akhil; Sebastian, Amritanand; Chen, Yifeng; et al. (ACS Nanoscience Au, 2022)
Since the isolation of graphene in 2004, two-dimensional (2D) materials research has rapidly evolved into an entire subdiscipline in the physical sciences with a wide range of emergent applications. The unique 2D structure offers an open canvas to tailor and functionalize 2D materials through layer number, defects, morphology, moiré pattern, strain, and other control knobs. Through this review, we aim to highlight the most recent discoveries in the following topics: theory-guided synthesis for enhanced control of 2D morphologies, quality, yield, as well as insights toward novel 2D materials; defect engineering to control and understand the role of various defects, including in situ and ex situ methods; and properties and applications that are related to moiré engineering, strain engineering, and artificial intelligence. Finally, we also provide our perspective on the challenges and opportunities in this fascinating field.